The Influence of Korean Drama on The Behavior of Housewife in Indonesia - Puspa Hastria Sayu Wiwit, Septimia (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Korean dramas nowadays never fail to appear on the social media homepages of women, from children, teenagers to young mothers and housewives. How drugged they are when they watch Korean dramas, both series and mini series. Drakor fever is often used as a nickname for its lovers. This study aims to describe the extent of the influence of Korean dramas on the behavior of housewives in Indonesia. The research method used is library research (Library Research) in which the author conducts a study and collects data sourced from the media of books, literature, notes, as well as relevant studies related to the research object to be studied. The results of this study are a discussion of what are the good and bad influences of the appearance of Korean dramas on the professionalism of a housewife Abstract a maximum of 250—300 words. The abstract contains a depiction of the research you are running. The abstract contains a summary of the introduction, the problems studied, the methods you used, and explains the results and discussion of the research carried out.